2021
DOI: 10.1097/mpg.0000000000003204
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Perspective of Coronavirus Disease 2019 in Children—An Updated Review

Abstract: Gastrointestinal symptoms are common findings in children with severe acute respiratory syndrome coronavirus 2 infection, including vomiting, diarrhoea, abdominal pain, and difficulty in feeding, although these symptoms tend to be mild. The hepato-biliary system and the pancreas may also be involved, usually with a mild elevation of transaminases and, rarely, pancreatitis. In contrast, a late hyper-inflammatory phenomenon, termed multisystem inflammatory syndrome (MIS-C), is characterized by more frequent gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 90 publications
0
30
0
2
Order By: Relevance
“…Data on GI manifestations of COVID-19 in the pediatric population seem to be conflicting. Although respiratory tract involvement is a typical clinical manifestation of SARS-COV 2 in adults, GI symptoms are more frequently reported in the pediatric population [51][52][53]. It has been observed that GI manifestations, such as diarrhoea and vomiting, are quite common at the disease presentation although less prominent in comparison to adults [12].…”
Section: Gastrointestinal Symptoms Of Severe Acute Respiratory Syndro...mentioning
confidence: 99%
“…Data on GI manifestations of COVID-19 in the pediatric population seem to be conflicting. Although respiratory tract involvement is a typical clinical manifestation of SARS-COV 2 in adults, GI symptoms are more frequently reported in the pediatric population [51][52][53]. It has been observed that GI manifestations, such as diarrhoea and vomiting, are quite common at the disease presentation although less prominent in comparison to adults [12].…”
Section: Gastrointestinal Symptoms Of Severe Acute Respiratory Syndro...mentioning
confidence: 99%
“…However, it has been shown that gastrointestinal manifestations are particularly frequent and prominent in children with PIMS-TS/MIS-C [ 6 ]. Thus, it may be challenging to differentiate this condition from an exacerbation of chronic inflammatory conditions including inflammatory bowel disease (IBD) [ 7 , 8 ]. Herein we aimed to present clinical characteristics and difficulties in the management of children with concurrent IBD and PIMS-TS/MIS-C based on our experience with four patients.…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory syndrome (fever, cough, respiratory difficulties) is the main feature and thus the main target for clinical screening of children with suspected COVID-19 [ 5 , 6 , 7 , 8 , 9 , 10 ]. Gastrointestinal (GI) symptoms related to COVID-19, such as vomiting, diarrhea, and abdominal pain, have emerged among extrapulmonary manifestations [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%